MBG Program: Identifying Values of Togetherness and Motivating Elementary School Student Attendance - Aulia , Wina Fadila; Muhardini, Sintayana; Fujjiaturrahman, Sukron (Moestopo International Review on Social, Humanities, and Sciences, 2026)
Free Nutritious Meal Programs generally aim to meet students’ nutritional needs and support their learning quality. These programs are often viewed as routine nutritional interventions that unconsciously foster character traits such as greater care and empathy in students. No studies have yet linked culturally and religiously based values of togetherness to changes in student behavior within the context of the Free Nutritious Meals Program (MBG). Therefore, this study was conducted to identify the values of togetherness and student attendance motivation formed through the implementation of the MBG Program in elementary schools. This study employed a descriptive qualitative approach. Research data were collected through observation, in-depth interviews, and document review. Data were analyzed using the Miles and Huberman interactive model, encompassing data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the MBG Program has proven effective in enhancing elementary students’ learning experiences. The routine of eating together fosters positive social interactions among students, and improved student attendance is evident in the increased consistency of students arriving early to participate in school activities; this behavior is shaped because the program serves as a motivator for students to ensure they do not arrive late.